The influence of macroeconomic - Reddy, Sugendree (My University, 2011)
This paper uses Fama and MacBeth (1973) methodology for deriving factor realisations from a group of economic indicators for the South African economy, in order to test the effect of economic factors on asset returns in an arbitrage pricing theory framework. Four factors were tested against the All share, Top 40, Industrial 25 and Resource 40 indices. No significant evidence was found of the gold price, foreign exchange rate, 10 year bond rate or prime overdraft rate factor beta coefficients having significant influence on asset returns in the four selected indices of the Johannesburg securities exchange for the period 1996 – 2008
MBA - WBS
Keywords: Johannesburg Securities Exchange; Macroeconomics